2013
DOI: 10.15376/biores.8.4.4969-4980
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Fungal Isolates for Biopulping of Rice Straw

Abstract: Sixty-two fungal isolates were screened for lignin peroxidase production. The most potent isolates for lignin peroxidase production were identified using the DNA sequence of the internal transcribed spacer (ITS) region as Phanerochaete chrysosporium and Pleurotus ostreatus. The pretreatment of rice straw with P. chrysosporium, Pl. ostreatus, or lignin peroxidase for use in the biopulping process was studied. Great variations in the loss of pulp yield and kappa number were recorded with different fungal and enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Other studies also showed that ramie biopulping (Boehmeria nivea) by Marasmius sp. reduced 8 points of Kappa Numbers from the control treatment during 7 days of incubation [22], and biopulping rice straw with Pleurotus ostreatus which Kappa Numbers reduced from 8.6 points to 7.8 points in 5 days incubation time [23]. Biodelignification of ramie chips using Penicillium sp.…”
Section: Ramie Pulpmentioning
confidence: 94%
“…Other studies also showed that ramie biopulping (Boehmeria nivea) by Marasmius sp. reduced 8 points of Kappa Numbers from the control treatment during 7 days of incubation [22], and biopulping rice straw with Pleurotus ostreatus which Kappa Numbers reduced from 8.6 points to 7.8 points in 5 days incubation time [23]. Biodelignification of ramie chips using Penicillium sp.…”
Section: Ramie Pulpmentioning
confidence: 94%
“…With regard to production and utilization of wood, decay is generally harmful and adverse, resulting in the decline of material properties. Decay is an inevitable process and it is not always disadvantageous to production; such as biopulping can be regarded as a decay under control for some microbial species only lead to lignin degradation in such a "decay" process (Badr El-Din et al 2013). Natural decay always happens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to wood, white rot fungi grows on a wide range of lignocellulose materials originating from agricultural waste that would otherwise present problems in disposal, and by means of the fungi these materials can be turned into useful products such as biofuels, animal feeds, or paper, or further biorefined into potentially valuable products (Sánchez 2009;Menon and Rao 2012). The growth of different types of white rot fungi has been examined on corn stover (Shrestha et al 2008), wheat straw (Hatakka 1983;Moyson and Verachtert 1991;Wan and Li 2010;Arora et al 2011;Shrivastava et al 2011), rice straw (El-Din et al 2013), ula grass (Carex meyeriana) (Mao et al 2013), and Bermuda grass (Gamble et al 1994).…”
Section: Introductionmentioning
confidence: 99%